(untitled) (Revista Contexto & Saúde, 2025)
Adolescence is marked by various biopsychosocial transformations that influence decision-making. The awakening of sexuality and early sexual initiation are factors that expose adolescents to vulnerable health situations. This study aims to understand the experiences and influencing factors related to the sexual initiation of adolescents within the context of sexual and gender diversity, through the lens of Madeleine Leininger’s theory. This qualitative study was conducted with adolescents from a public school in Recife, Pernambuco, Brazil, using semi-structured interviews carried out between June and December 2019. The results were analyzed using Bardin’s content analysis and processed with IRaMuTeQ through the similarity analysis interface. Three thematic axes emerged: Factors contributing to early sexual initiation; Conflicts related to sexual orientation, gender identity, and gender expression; and Knowledge about sexual and reproductive health. Early sexual initiation among adolescents is not limited to chronological age, as recognizing vulnerability factors may support a better understanding of sexuality in the context of sexual and gender diversity.